Enhanced Predictive Torque Control for Three-Level NPC Inverter-Fed PMSM Drives Based on Optimal Voltage Magnitude Control Method - Hakami, Samer Saleh; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2023)
The major drawback of conventional predictive torque control (PTC) is that it fixes the magnitude of the reference voltage vector (VV) to 70%. This limitation results in large torque and flux ripples and slow dynamic response, especially when the permanent magnet synchronous motor operates in low-speed regions. A promising approach for reducing torque and flux ripples is by replacing the two-level inverter with a three-level neutral-point-clamped (NPC) inverter. Nevertheless, because of the elimination of zero VV during torque decrement in a conventional PTC, a large torque ripple appears in the low-speed region. In addition, high-speed operation is not applicable unless more dc-link is injected. To solve these problems, an effective, creative, and low-complex PTC based on a reference voltage vector magnitude control method (RVVCM) is proposed in this article. The proposed PTC effectively minimizes torque and flux ripples by utilizing only the required magnitude of reference VV of the three-level NPC inverter based on the variable voltage control concept. Furthermore, the dynamic response of the torque is improved by applying the full magnitude of applied VV. Simulation and experimental results are presented to validate the effectiveness of the proposed RVVCM-based PTC algorithm.
Keywords: Fast dynamics; Inverter; Permanent magnet synchronoi motor; Permanent Magnet Synchronous Motor; Predictive torque control; Predictive torque controls; Reference voltage vector; Reference voltages; Space vector pulse width modulation; Torque-ripple reduction; Voltage vectors; Fast dynamics; permanent magnet synchronous motor (PMSM); predictive torque control (PTC); reference voltage vector (VV); space vector pulsewidth modulation (SVPWM); torque ripple reduction